PENGARUH PEMBERIAN EKSTRAK IKAN GABUS TERHADAP KADAR INTERLEUKIN – 6 PADA IBU NIFAS DENGAN RUPTURE PERINEUM - Irmayanti. A.Oka (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2016)
The research aimed at investigating the effect of the cork fish extract delivery on the interleukin-6 content change on the parturition women with the rupture perineum in the Specific Hospital of Mother and Child, Sitti Fatimah, Makassar. This was the quasi experimental research with the pre-post tes group design taken from the parturition women with the rupture perineum. Sample were as many as 30, in wich 15 the parturition women with the rupture perineum of degree II who were given the cork fish extract as the intervention were give Health Education as the control group. The measurement of IL-6 content was conducted one day post partum and after 7 das treatment. The data were analysed using Wilcoxon test and Mann-Whitney test. The research result indicated that there is the significant effect of the cork fish extract delivery on the decrease of IL-6 content namely: the intervention group is p= 0.02 and control group is p=1.00. Keyword : Cork fish extract, IL-6 content, parturition women